2021
DOI: 10.3389/fimmu.2021.654998
|View full text |Cite
|
Sign up to set email alerts
|

HCV Core Protein Induces Chemokine CCL2 and CXCL10 Expression Through NF-κB Signaling Pathway in Macrophages

Abstract: HCV core protein is the first structural protein synthesized during hepatitis C virus (HCV) infection and replication. It is released from virus infected liver cells and mediates multiple functions to affect host cell response. The innate immune response is the first line of defense against viral infection. After HCV infection, Kupffer cells (KCs) which are liver macrophages play an important role in host innate immune response. Kupffer cells act as phagocytes and release different cytokines and chemokines to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…In addition, chemokines, C–C motif chemokine ligand (CCL)-2 [ 7 ] and C-X-C motif chemokine ligand (CXCL)-10 [ 8 ], have been reported to be associated with Th1 immune responses. A recent report also found that the induction of CCL2 and CXCL10 secretions in macrophages exaggerated the host-derived immune responses [ 9 ]. Moreover, the heterogeneity of macrophage polarization plays a critical role in several diseases, such as atherosclerosis [ 10 ], pulmonary infection [ 11 ], and obesity-associated metabolic diseases [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chemokines, C–C motif chemokine ligand (CCL)-2 [ 7 ] and C-X-C motif chemokine ligand (CXCL)-10 [ 8 ], have been reported to be associated with Th1 immune responses. A recent report also found that the induction of CCL2 and CXCL10 secretions in macrophages exaggerated the host-derived immune responses [ 9 ]. Moreover, the heterogeneity of macrophage polarization plays a critical role in several diseases, such as atherosclerosis [ 10 ], pulmonary infection [ 11 ], and obesity-associated metabolic diseases [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another worthy topic in this study is that several CXCL family members may have the potential to interact with viral proteins. It was reported that hepatitis C virus (HCV) core protein could induce CXCL10 expression through NF-κB signaling pathway in macrophages [ 46 ]. CXCL10 is a marker of host immune response, which is dependent on interferon (IFN)—γ [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that STAT1 may reduce liver fibrosis by inhibiting HSC proliferation and stimulating NK cells to destroy activated HSC ( 26 ). CXCL10 can have an expressional induction after viral stimulation of the liver ( 27 ). Several studies have suggested that CXCL10 is associated with viral liver fibrosis ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%